2020
DOI: 10.1371/journal.pone.0240669
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban improves vascular response in LPS-induced acute inflammation in experimental models

Abstract: Rivaroxaban (RVX) was suggested to possess anti-inflammatory and vascular tone modulatory effects. The goal of this study was to investigate whether RVX impacts lipopolysaccharide (LPS)-induced acute vascular inflammatory response. Male rats were treated with 5 mg/kg RVX (oral gavage) followed by 10 mg/kg LPS i.p injection. Circulating levels of IL-6, MCP-1, VCAM-1, and ICAM-1 were measured in plasma 6 and 24 hours after LPS injection, while isolated aorta was used for gene expression analysis, immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
0
16
2
Order By: Relevance
“…A treatment effect vs aspirin is difficult to obtain since aspirin itself is a potent anti-inflammatory drug. This finding is in contrast to animal studies which demonstrated a significant reduction of MCP-1 and IL-6 plasma levels with rivaroxaban treatment [36]; however, most of these studies were of short duration and induced acute inflammatory responses. One recently published trial of 918 individuals with atrial fibrillation reported a small but statistically significant 10% reduction of hsCRP and IL-6 plasma levels after 42 days of rivaroxaban treatment [39]; however, all patients received electrical cardioversion which could have influenced the results.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…A treatment effect vs aspirin is difficult to obtain since aspirin itself is a potent anti-inflammatory drug. This finding is in contrast to animal studies which demonstrated a significant reduction of MCP-1 and IL-6 plasma levels with rivaroxaban treatment [36]; however, most of these studies were of short duration and induced acute inflammatory responses. One recently published trial of 918 individuals with atrial fibrillation reported a small but statistically significant 10% reduction of hsCRP and IL-6 plasma levels after 42 days of rivaroxaban treatment [39]; however, all patients received electrical cardioversion which could have influenced the results.…”
Section: Discussioncontrasting
confidence: 94%
“…We did not find any effect on VASP Ser 157 phosphorylation, VCAM-1, ICAM-1 or 3-nitrotyrosine. This is in contrast to recently published data in animal models [36] or cell culture [32] which demonstrated a reduction of circulating VCAM-1 and ICAM-1 levels or mRNA; however, these studies used lipopolysaccharide or thrombin for acute induction of these adhesion molecules to a level tenfold or 100-fold above baseline, which is far beyond a physiological level in humans. In addition, there is a remarkable endothelial cell heterogeneity even within an organ system and the degree of endothelial dysfunction can vary between different vascular regions depending on the microenvironment [37].…”
Section: Discussioncontrasting
confidence: 90%
“…Previous data show, that the levels of inflammatory cytokines such as IL‐1β, IL‐6 and TNF‐α were significantly lower in HUVECs stimulated with FXa + rivaroxaban + LPS as compared to FXa + LPS stimulation. Furthermore, pre‐treatment with rivaroxaban significantly reduced IL‐6, MCP‐1 and VCAM‐1 plasma concentration 6 and 24 hours after LPS injection 13 . Paar et al 25 report that dabigatran treatment may halt the secretion of IL‐6, IL‐8, vascular endothelial growth factor (VEGF) and MCP‐1 in supernatant from peripheral blood mononuclear cell (PBMC) pre‐treated with 200 ng/mL thrombin; however, dabigatran was found to have no effect on the expression of TNFα or IL‐1.…”
Section: Discussionmentioning
confidence: 91%
“…Soh et al 24 showed that endothelial cells that had been treated with 7‐ketocholesterol showed a 4.6‐fold increase in eNOS mRNA expression, and a larger 10.4‐fold increase in inducible NO synthase (iNOS) mRNA expression. Dabigatran was found to significantly enhance catalase and superoxide dismutase activity and suppress iNOS in a rabbit model of acute myocardial infarction, 14 also rivaroxaban reduced iNOS, MCP‐1 and VCAM‐1 expression in vascular endothelium inducted by LPS 13 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation